Accounting for photosystem I photoinhibition sheds new light on seasonal acclimation strategies of boreal conifers - Grebe, Steffen; Porcar-Castell, Albert; Riikonen, Anu; Paakkarinen, Virpi; Aro, Eva-Mari (Oxford University Press, 2025)
The photosynthetic acclimation of boreal evergreen conifers is controlled by regulatory and photoprotective mechanisms that allow conifers to cope with extreme environmental changes. However, the underlying dynamics of photosystem II (PSII) and photosystem I (PSI) remain unresolved. Here, we investigated the dynamics of PSII and PSI during the spring recovery of photosynthesis in Pinus sylvestris and Picea abies using a combination of chlorophyll-a fluorescence, P700 difference absorbance measurements, and quantification of key thylakoid protein abundances. In particular, we derived a new set of PSI quantum yield equations, correcting for the effects of PSI photoinhibition. Using the corrected equations, we found that the seasonal dynamics of PSII and PSI photochemical yields remained largely in balance, despite substantial seasonal changes in the stoichiometry of PSII and PSI core complexes driven by PSI photoinhibition. Similarly, the previously reported seasonal upregulation of cyclic electron flow was no longer evident, after accounting for PSI photoinhibition. Overall, our results emphasize the importance of considering the dynamics of PSII and PSI to elucidate the seasonal acclimation of photosynthesis in overwintering evergreens. Beyond the scope of conifers, our corrected PSI quantum yields expand the toolkit for future studies aimed at elucidating the dynamic regulation of PSI.